Snow in a Very Steep Rock Face: Accumulation and Redistribution During and After a Snowfall Event - Sommer, Christian G.; Lehning, Michael; Mott, Rebecca (Frontiers in Earth Science, 2015)
Terrestrial laser scanning was used to measure snow thickness changes (perpendicular to the surface) in a rock face. The aim was to investigate the accumulation and redistribution of snow in extremely steep terrain (>60°). The north-east face of the Chlein Schiahorn in the region of Davos in eastern Switzerland was scanned before and several times after a snowfall event. A summer scan without snow was acquired to calculate the total snow thickness. An improved postprocessing procedure is introduced. The data quality could be increased by using snow thickness instead of snow depth (measured vertically) and by consistently applying Multi Station Adjustment to improve the registration. More snow was deposited in the flatter, smoother areas of the rock face. The spatial variability of the snow thickness change was high. The spatial patterns of the total snow thickness were similar to those of the snow thickness change. The correlation coefficient between them was 0.86. The fresh snow was partly redistributed from extremely steep to flatter terrain, presumably mostly through avalanching. The redistribution started during the snowfall and ended several days later. Snow was able to accumulate permanently at every slope angle. The amount of snow in extremely steep terrain was limited but not negligible. Areas steeper than 60° received 15% of the snowfall and contained 10% of the total amount of snow.